Exploring the correlation between collocational mastery and Japanese language proficiency levels - Firmansyah, Dian Bayu; Haryono, Haryono; Hariyadi, Bagus Reza (Universitas Dian Nuswantoro, 2025)
Mastering collocation is a crucial aspect of second language acquisition at the B2 level, particularly in Japanese. Understanding collocation allows learners to comprehend common word combinations used in everyday conversation. This study aims to explore the understanding of collocation among Japanese language learners and to identify errors in their sentence construction. Using a mixed-method approach, the research includes collocation knowledge tests, questionnaires, and interviews to collect data from Japanese language learners in Indonesia. The findings indicate that many learners struggle with proper collocation usage, largely due to the influence of their native language and a limited understanding of suitable word combinations in Japanese. However, with effective teaching methods and consistent practice, learners can improve their grasp of collocation, which will lead to more effective and natural communication in Japanese. This study concludes that a strong command of collocation significantly enhances Japanese language proficiency, particularly in terms of fluency and contextual understanding. The research intends to contribute to the development of collaborative learning strategies in Japanese, especially for non-native speakers, to facilitate daily communication in the language.